ONGs e internet: da ação educativa e política no lugar ao ciberespaço - Sousa, Carlos Alberto Lopes de (2005)
What conditions can NGOs create to implement educational and political projects through the Internet? What risks or consequences can NGOs face from their actions taken through the informational flows from a location to cyberspace? These are some of the questions discussed in the thesis. The research presents a theoretical discussion based on Shaff (1995), Lojkine (1995), Castells (1999) e Giddens (1991) views of societies (information society, informatics society, informational revolution, modernity). The study adopts Giddens (2002) conception that modern social life is characterized by processes of time and space reorganization, which are associated to the mechanisms of mismatch that shifts the social relations from their specific locations, recombining themselves after covering great distances in time and space. The description of the educational and political actions taken by the Brazilian Institute pf Social and Economic Analyses - IBASE (RJ); the Centre for the Defense of Human Rights and Preservation of Indigenous Memory CDDHMP (RN) and the Committee for Democratization of Informatics CDI (SP) allowed me to analyse the informational flows between location and cyberspace. The research follows a reflective, interpretive perspective, performing bibliographical and documental analysis, interviews and in loci visits to the NGOs headquarters. The thesis concludes that the actions taken by the NGOs through the Internet caused the emergence of contradictions directly related to, among others, the NGOs conditions to operate the Internet and the way they structured their actions. From the process of reflection concerning the advantages Internet brought to the NGOs, idealized or implemented in educational and political actions, emerged, as a perspective from the risk and consequence to these entities, the perspective of working under the Presence Saving logic.